SNEDDS Containing Poorly Water Soluble Cinnarizine; Development and in Vitro Characterization of Dispersion, Digestion and Solubilization - Anne T. Larsen; Anette Müllertz; Ragheb Abu-Rmaileh; Bertil Abrahamsson; Jesper Østergaard; Anayo Ogbonna (MDPI AG, 2012)
Self-Nanoemulsifying Drug Delivery Systems (SNEDDSs) were developed using well-defined excipients with the objective of mimicking digested SNEDDSs without the use of enzymes and in vitro lipolysis models and thereby enabling studies of the morphology and size of nanoemulsions as well as digested nanoemulsions by Cryo-TEM imaging and Dynamic Light Scattering. Four SNEDDSs (I-IV) were developed. Going from SNEDDS I to IV lipid content and solubility of the model drug cinnarizine decreased, which was also the case for dispersion time and droplet size. Droplet size of all SNEDDS was evaluated at 1% (w/w) dispersion under different conditions. Cinnarizine incorporation increased the droplet size of SNEDDSs I and II whereas for SNEDDSs III and IV no difference was observed. At low pH cinnarizine had no effect on droplet size, probably due to increased aqueous solubility and partitioning into the aqueous phase. Dispersion of the SNEDDSs in Simulated Intestinal Media (SIM) containing bile salts and phospholipids resulted in a decrease in droplet size for all SNEDDS, as compared to dispersion in buffer. Increasing the bile salt/phospholipid content in the SIM decreased the droplet sizes further. Mimicked digested SNEDDS with highest lipid content (I and II) formed smaller nanoemulsion droplet sizes upon dispersion in SIM, whereas droplet size from III and IV were virtually unchanged by digestion. Increasing the bile acid/phosphatidylcholine content in the SIM generally decreased droplet size, due to the solubilizing power of the endogenous surfactants. Digestion of SNEDDSs II resulted in formation of vesicles or micelles in fasted and fed state SIM, respectively. The developed and characterized SNEDDS provide for a better knowledge of the colloid phases generated during digestion of SNEDDS and therefore will enable studies that may yield a more detailed understanding of SNEDDS performance.